(untitled) (Zeitschrift für Migrationsforschung, 2025)
Negotiation (Aushandlung) has become a central element of the longer-lasting endeavor to carve out the dynamics, mechanisms, and functions of the societal »production of migration«. One of the scholars who has continuously shaped and reflected on this is Jochen Oltmer. On the occasion of his 60th birthday, this issue starts a discussion based on one of his key articles on migration regimes and the negotiation of migration translated into English (»Migration aushandeln« 2018), followed by five contributions that engage from different epistemic, disciplinary, and methodical perspectives with the concept of negotiation as developed by Jochen Oltmer. They address key questions on the concept’s analytical benefits and discuss its prospects and limits, especially regarding historical and contemporary perspectives on migration and (post-)migrant societies. Migration aushandeln: Eine kritische Würdigung von Jochen Oltmers Konzept der Aushandlung. Eine Einführung Das Konzept der Aushandlung von Migration ist zu einem zentralen Element der längerfristigen Bemühungen geworden, die Dynamiken, Mechanismen und Funktionen der gesellschaftlichen »Produktion von Migration« herauszuarbeiten. Maßgeblich geprägt und fortlaufend reflektiert wurde und wird das Konzept von Jochen Oltmer. Anlässlich seines 60. Geburtstags beginnen wir in dieser Ausgabe eine Diskussion über Potentiale und Grenzen des Konzepts für die Migrationsforschung: Welche analytischen Vorteile gewährt die Perspektive der Aushandlung? Wie passen historische und gegenwärtige Deutungsrahmen zusammen und was bedeutet das für unsere Debatten in Migrations- oder auch postmigrantischen Gesellschaften? Auf Grundlage des ins Englische übersetzten Aufsatzes »Migration aushandeln« (2018) von Jochen Oltmer versammelt das vorliegende Heft hierzu fünf unterschiedliche epistemologische, disziplinäre und methodische Perspektiven auf Aushandlung.